A new reconstruction of atmospheric gaseous elemental mercury trend over the last 60 years from Greenland firn records. (July 2016) - Dommergue, A.; Martinerie, P.; Courteaud, J.; Witrant, E.; Etheridge, D.M.
Abstract: This study presents measurements of gaseous elemental mercury (GEM) concentrations in the 80 m of firn air at the international drilling site of NEEM in Greenland (2452 m, 77°25.8 N, 51°06.4 W). Using inverse modeling, we were able to reconstruct the atmospheric GEM trend at this Arctic site over the last 60 years. We show discrepancies between this record and the previous firn record of Summit. This could be attributed to experimental biases and/or differences in air mass transport. A multisite inverse model was used to derive an atmospheric scenario reconciling the two firn records. We show that GEM seasonal variations are very limited at these high altitude sites and thus probably unaffected by spring/summer photochemistry. The firn reconstructions suggest an increase of GEM concentrations since the 1950s peaking in the late 1960s and early 1970s. A decrease is then observed with minimum GEM concentrations around 1995–2000. The reconstruction compares well with historical mercury (Hg) releases and recent simulations of atmospheric Hg. Our optimal GEM scenario does not allow to categorically conclude on recent trends for GEM concentrations over the 2000–2010 decade. Highlights: Reconstruction of atmospheric gaseous mercury trend in the Arctic over 60 years. The absence of strong seasonal variations for atmospheric GEM. The optimal scenario is consistent with historical releases and model simulations.